2021
DOI: 10.3390/su13021003
|View full text |Cite
|
Sign up to set email alerts
|

Partner Selection in China Interorganizational Patent Cooperation Network Based on Link Prediction Approaches

Abstract: To enhance competitiveness and protect interest, an increasing number of organizations cooperate on patent applications. Partner selection has attracted much more attention because it directly affects the success of patent cooperation. By collecting some cooperative patents applied for by different categories of organizations in China from 2007 to 2015, an interorganizational patent cooperation network was built for this paper. After analyzing certain basic properties of the network, it was found that the netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In terms of research methods, the partner selection method mainly focuses on the multi-attribute decision making method (Mousavi and Gitinavard, 2019;Zeng et al, 2019), network correlation analysis method (Chen et al, 2021), SEM method (Hair et al, 2019), VIKOR group decision making method (Wang et al, 2019), mathematical analysis method (Bolandnazar et al, 2020), intuitionistic fuzzy theory (Yang et al, 2021), method set (Venkatesh et al, 2019), and stage method (Ávila et al, 2021). For example, Mousavi and Gitinavard (2019) extended a multi-attribute group decision approach for the selection of outsourcing service activities for information technology under risk.…”
Section: Partner Selection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of research methods, the partner selection method mainly focuses on the multi-attribute decision making method (Mousavi and Gitinavard, 2019;Zeng et al, 2019), network correlation analysis method (Chen et al, 2021), SEM method (Hair et al, 2019), VIKOR group decision making method (Wang et al, 2019), mathematical analysis method (Bolandnazar et al, 2020), intuitionistic fuzzy theory (Yang et al, 2021), method set (Venkatesh et al, 2019), and stage method (Ávila et al, 2021). For example, Mousavi and Gitinavard (2019) extended a multi-attribute group decision approach for the selection of outsourcing service activities for information technology under risk.…”
Section: Partner Selection Methodsmentioning
confidence: 99%
“…Zheng et al used expert evaluation and system analysis methods to conduct a comprehensive evaluation on the selection of partners. Chen et al (2021) summarized that quality and capability are the main indicators for the evaluation of industry-university-research collaborative innovation partners. Su et al (2022) found that core members will preferentially select collaborative members with knowledge stock advantages to form a knowledge supply chain.…”
Section: Partner Selection Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing research, a series of approaches have been proposed for studying on partner selection in cooperation networks, which can be mainly classified into two families: location-based collaboration and competency-based collaboration. In the early years, limited by undeveloped communication technology and expensive transportation costs, the geographical locations of cooperators is crucial for the selection of partners [30]. Evolution analysis of cooperation networks is very beneficial for the prediction of potential partners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for research on the cooperation network of tourism attractions, most of the previous studies on the government's policies or measures for the cooperation of tourism attractions are from the perspective of supply [14][15][16][17][18][19][20][21]. The cooperation network of tourist attractions is closely related to tourism flow [22][23][24][25][26][27]. On the demand side, the spatial decisionmaking behavior of tourists influences the form, scope, and structure of the cooperation network between tourist attractions.…”
Section: Introductionmentioning
confidence: 99%